Imunomodulator Activity of Three Types “Kayu Kuning” Borneo - Dwi Hadi Setya Palupi; Riski Sulistiarini; Vita Olivia Siregar (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2022)
The immune system is a system that plays a role in maintaining the integrity of the body against the dangers that various foreign objects can cause. Immunomodulators are substances or substances that can change/modify the immune system. Empirically, Kayu Kuning or Yellow Wood is used as a cleaner for post-partum conditions. Yellow wood in East Kalimantan is the name for three species, namely Arcangelisia Flava, Fibraurea tinctoria, and Coscinium fensteratum. With the approach of improving the immune system and metabolism, immunomodulatory tests carried out on three types of yellow wood found in Borneo Island. The immunomodulatory activity of Yellow wood steam extract in the non-specific immune response test used phagocytic index and organ index parameters where BALB/c female mice were randomly divided into 16 treatment groups which included a normal group, an immunostimulant comparison group (Levamisole 2.5 mg/kg body weight), an immunosuppressant comparison group (Methylprednisolone 40mg/kg BW), a test extract group with a dose of 100 mg/kg body weight, for the ethanolic extracts of A. Flava, F. tinctoria and C. fenestratum, respectively. Based on the study results, it means that the methanol extract of A. Flava methanol extract had immunostimulating activity, while the methanol extract of F. tinctoria and C. fenestratum showed an immunosuppressant effect